A description and explanation of the complex landscape of faith-based organisations in Cameroon's health sector. Issue 3 (3rd April 2021) - Herzig van Wees, Sibylle; Betsi, Emmanuel; Sop Sop, Maturin Désiré
ABSTRACT: Over the past decade, donors have engaged faith-based organisations (FBOs) in health system reforms and health programmes in many sub-Saharan African countries, including Cameroon. Little knowledge is available concerning the types of FBOs that exist in the health sector in Cameroon. This article describes the complex landscape of Christian FBOs operating in Cameroon's health sector and provides an explanation for that diversity. It reflects on the implications of the use of the "FBO" acronym in Cameroon and argues that the FBO typology discussion is still relevant.